Experimental Investigation of Nano Iron Oxide on Physical Properties of Salt-Saturated Drilling Mud (Journal of Engineering, 2025)
The process of drilling wells has become more complex today due to greater depths and advanced drilling techniques. Therefore, obtaining ideal specifications for drilling fluids has become of great importance to overcome drilling problems and reduce costs. Therefore, studies have begun to investigate the effect of nanomaterials on drilling fluids. This study is an investigation into the effect of nano-iron oxide on drilling fluid specifications. Saturated salt mud was used, and different physical properties such as viscosity, density, and filtrate loss were measured at different temperatures (30 ˚C, 50 ˚C, and 70 ˚C), and adding different proportions of nano iron oxide (0.75 and 1.5 gm). This study is characterized by the combination of field and laboratory work. The addition of nano iron oxide leads to an increase in gel strength while the other rheological properties remained relatively constant, and the change in filtration and mud cake is small except at high temperature. Rising temperature leads to a decrease in rheological properties, except for gel strength. But at 70 C˚, the addition of nano iron oxide reduced the effect of rising temperature, especially on the yield point, and this is an important property when drilling a salt section.